Mewujudkan Tata Kelola Keuangan Desa Yang Transparan: Analisis Akuntabilitas Pengelolaan Alokasi Dana Desa Di Desa Sesulu, Kecamatan Waru - Yudea, Yudea; Hendrawan, Yudhi; Syaripah Fitriani, Siti (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2026)
This study analyzes the accountability of Village Fund Allocation (VFA) management in Sesulu Village, Waru District, Penajam Paser Utara Regency, through three crucial phases: planning, implementation, and accountability. Employing a descriptive qualitative approach, data were gathered via in-depth interviews with key stakeholders, participatory observation, and official document analysis. Findings indicate that the planning stage was conducted participatively and transparently, although varying levels of public understanding limited more inclusive participation. Program implementation generally adhered to regulations, but encountered operational constraints such as delayed fund disbursement and limited technical capacity of village officials. Accountability in the reporting phase demonstrated a commitment to transparency through public reporting, yet challenges persisted regarding document completeness and reporting timeliness. This study concludes that the principles of good governance have been reasonably implemented, but substantial improvements are required in institutional capacity, inclusive community participation, and the strengthening of oversight mechanisms. Future research is recommended to explore the contribution of public budget literacy or the implementation of digital technologies in optimizing the transparency of village financial management.